Penerapan Metode Wahdah Pada Program Tahfidz Qur’an Di Rumah Tahfidz Al-Ihsan Desa Sordang Bolon - Fitri Tanjung, Ellisa; Isnaini, Putri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
One way for us to maintain the sanctity of the Qur’an is to memorize its words properly and correctly. The implementation of memorizing the Qur’an, especially in elementary schools/Madrasahs other than Islamic boarding schools, certainly requires preparation both mentally and physically. As has been implemented at the Tahfidz Al-Ihsan House, the ustadzah applies a special method for memorizing so that students can feel comfortable and not get bored of memorizing. This research aims to determine the application of the wahdah method at the Tahfidz Al-Ihsan House and the results after applying the wahdah method at the Tahfidz Al-Ihsan House. This research is field research using descriptive qualitative research, namely a series of data collection processes, combining and drawing conclusions about the data. Data collected through observation, documentation and interviews. The research results state that the application of the wahdah method used to improve the results of memorizing the Koran for students who have difficulty memorizing has shown results compared to before. The results of the research show that the wahdah method is a suitable method for memorizing at the Tahfidz Al-Ihsan House. Santri and ustadzah don’t really encounter any difficulties when using this method. Indeed, there are several difficulties encountered by ustadzah and students, such as sometimes not having enough time to complete memorization. However, this can be overcome by telling students to continue memorizing at home and deposit it again the next day before starting learning.